COMMUNICATING LOCAL WISDOM IN DEVELOPING VILLAGE REGULATIONS ON SUSTAINABLE TOURISM DEVELOPMENT - Diyah Indiyati; Hartin Nur Khusnia; Siti Chotijah; Muhlis (JOSAR (Journal of Students Academic Research), 2021)
Tourism is considered as one of the hopes in economic growth both at the national level and at the local level. A number of local tourism spots continue to be introduced to increase the number of tourist visits. However, the growth of tourism targeting massive tourism will certainly have a diverse impact, not only a positive impact but also the potential to bring excesses that affect the community in socio-economic aspects. People learn that something that grows quickly will ignite social change which sometimes clash with the values ​​of local wisdom that were first present in the community. This study aims to find out how local wisdom communicate within the community to be integrated with policies at the rural level in the form of rural regulations in developing sustainable tourism. This study uses an action research method case study of Lantan Tourism Village which is located in the southern belt of Rinjani. The results shown are that the tourism village community has the potential to actively participate in formulating policy making, but there are some local wisdoms that have encountered obstacles to be harmonized with applicable regulations when linked to sustainable tourism. A number of issues have emerged, including identification of ongoing communication patterns, communication barriers, identification of potentials, identification of local wisdom